1998
DOI: 10.1590/s0102-311x1998000700012
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian cohort of pulp and paper workers: the logistic of a cancer mortality study

Abstract: The International Agency for Re s e a rch on Cancer (IARC) proposed this international historical cohort study trying to solve the controversy about the increased risk of cancer in the w o rkers of the Pulp and Paper In d u s t ry. One of the most important aspects presented by this Key words Ep i d e m i o l o gy ; C o h o rt St u d i e s ; Data Sourc e s ; Ne o p l a s m s Resumo A Agência Internacional para Pesquisa sobre Câncer (IARC) propôs uma coorte históri-ca internacional para tentar re s o l ver a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Results based on national components of the multicenter cohort have been reported (Andersson et al 1998;Fassa et al 1998;Henneberger and Lax 1998;Henneberger et al 1989;Jäppinen and Pukkala 1991;Jäppinen and Tola 1986;Andersen 1999, 2000;Rix et al 1997Rix et al , 1998Sala-Serra et al 1996;Szadkowska-Stanczyk and Szymczak 2001;Szadkowska-Stanczyk et al 1997;Wild et al 1998). Assessment of exposure to specific agents was conducted by an international panel of industrial hygienists (Kauppinen et al 1997).…”
mentioning
confidence: 98%
“…Results based on national components of the multicenter cohort have been reported (Andersson et al 1998;Fassa et al 1998;Henneberger and Lax 1998;Henneberger et al 1989;Jäppinen and Pukkala 1991;Jäppinen and Tola 1986;Andersen 1999, 2000;Rix et al 1997Rix et al , 1998Sala-Serra et al 1996;Szadkowska-Stanczyk and Szymczak 2001;Szadkowska-Stanczyk et al 1997;Wild et al 1998). Assessment of exposure to specific agents was conducted by an international panel of industrial hygienists (Kauppinen et al 1997).…”
mentioning
confidence: 98%
“…This study has combined cohorts from 13 countries, consisting of 98,665 workers (2,110,913 person-years), and included the development of a comprehensive database of exposure measurements for the retrospective assessment of study participants’ exposure ( Kauppinen et al 1997 , 2002 ). The results for mortality and incidence in selected national cohorts ( Fassa et al 1998 ; Henneberger and Lax 1998 ; Henneberger et al 1989 ; Jäppinen and Pukkala 1991 ; Jäppinen and Tola 1986 ; Langseth and Andersen 1999 , 2000 ; McLean et al 2002 ; Rix et al 1997 , 1998 ; Sala-Serra et al 1996 ; Szadkowska-Stanczyk et al 1997 ; Szadkowska-Stanczyk and Szymczak 2001 ; Wild et al 1998 ), and for separate analyses of exposure to sulfur dioxide ( Lee et al 2002 ) and asbestos ( Carel et al 2002 ) in the overall cohort, have been reported.…”
mentioning
confidence: 99%
“…Soares et al, (2008) stated that individuals who work under extreme conditions especially overly high or low temperatures will experience a higher prevalence of lowerextremity musculoskeletal pain. Fassa et al, (1996) stated that extreme temperature contributes toward the unbalance of homeostasis and leads to metabolic derangements causing inflammation within the musculoskeletal and difficulty in rebuilding muscle.…”
Section: Risk Factors Affecting Msds Task Characteristics and Msdsmentioning
confidence: 99%